1998
DOI: 10.1021/jp971778i
|View full text |Cite
|
Sign up to set email alerts
|

Third-Order Nonlinear Optical Properties in the Excited State of Well-Defined Thiophene−Dimethylsilyl Co-oligomers

Abstract: A new series of oligomers for nonlinear optics (NLO), the thiophene−dimethylsilyl co-oligomers, (TSi) n −T with n = 1−3, have been synthesized in order to combine third-order NLO response and transparency in the visible region. Stationary-state absorption spectra, fluorescence spectra, and time-resolved absorption (picosecond) have been carried out. In sharp contrast with oligothiophenes, the absorption spectra of (TSi) n −T are not red-shifted as n increases, but as for short oligothiophenes their quantum yie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 43 publications
(79 reference statements)
0
18
0
Order By: Relevance
“…ethynylbenzene in hexane: k max = 236 nm, e max = 12 500 m -1 cm -1 ). It has been reported that diarylsilanes (e. g., 4,49-substituted dimethyldiphenylsilane [19] and dimethyldithienylsilane [20] ) and hyper- branched poly(2,5-silylthiophenes) [5] show p-to-r charge transfer absorptions in the range 300-320 nm. Poly(1) displays a weak absorption around 330 nm, which is clearer and stronger than that of poly (2).…”
Section: Resultsmentioning
confidence: 99%
“…ethynylbenzene in hexane: k max = 236 nm, e max = 12 500 m -1 cm -1 ). It has been reported that diarylsilanes (e. g., 4,49-substituted dimethyldiphenylsilane [19] and dimethyldithienylsilane [20] ) and hyper- branched poly(2,5-silylthiophenes) [5] show p-to-r charge transfer absorptions in the range 300-320 nm. Poly(1) displays a weak absorption around 330 nm, which is clearer and stronger than that of poly (2).…”
Section: Resultsmentioning
confidence: 99%
“…The interaction between the silylene group and the conjugated p-chromophore, if any, would be very weak. [11][12][13] For example, the very weak absorption at 310 nm for thiophene-dimethylsilylene co-oligomers 9 may arise from the transition involving charge transfer from the thiophene moiety to the dimethylsilylene group. 11 In addition, the weak Scheme 2 Scheme 1 absorption around 345 nm and structureless emission in a series of diphenylacetylene-dialkylsilylene copolymers 10 may be attributed to possible intramolecular charge transfer.…”
Section: Role Of Monosilylene Moiety On Photophysical Properties Of M...mentioning
confidence: 99%
“…[11][12][13] For example, the very weak absorption at 310 nm for thiophene-dimethylsilylene co-oligomers 9 may arise from the transition involving charge transfer from the thiophene moiety to the dimethylsilylene group. 11 In addition, the weak Scheme 2 Scheme 1 absorption around 345 nm and structureless emission in a series of diphenylacetylene-dialkylsilylene copolymers 10 may be attributed to possible intramolecular charge transfer. 12 As mentioned earlier, when the conjugation length is increased, the s-p interaction between the silylene group and the oligothiophene moiety may become less important.…”
Section: Role Of Monosilylene Moiety On Photophysical Properties Of M...mentioning
confidence: 99%
See 2 more Smart Citations